Penggunaan Aplikasi Quizizz dalam Meningkatkan Minat dan Hasil Belajar Siswa pada Mata Pelajaran Ekonomi Kelas XI di SMAN 1 Sutojayan - Della Eka Eliana; Dita Hendriani (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This study was motivated by the low interest and learning outcomes of students in Economics subjects at SMAN 1 Sutojayan. The purpose of the study was to determine the effect of using the Quizizz application on learning interest, learning outcomes, and both simultaneously in class XI students. The method used was quantitative with a quasi-experimental design, involving 60 students from two classes. Data were collected through questionnaires and tests, then analyzed using the t test of two independent samples and the MANOVA test. The results showed that the Quizizz application had a significant effect on increasing students' learning interest and learning outcomes, with a significance value of 0.002 for the t test and 0.000 for the MANOVA test, respectively. this study shows that the use of interactive learning media such as Quizizz is effective in increasing student learning engagement and achievement.